FAKTOR-FAKTOR YANG MEMPENGARUHI INTENTION TO DONATE MELALUI PLATFORM CROWDFUNDING - Adinda Nur Afifah; Andi Muhammad Sadat; Terrylina Arvinta Monoarfa (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study aims to identify the factors that influence the intention to donate or the intention to donate through a crowdfunding platform. The research method used was quantitative involving a sample of 216 respondents, and a pre-test was carried out on 30 respondents who are Jabodetabek people who know the crowdfunding platform as a means of donation. The data collection method in this study used a survey method by distributing questionnaires online. Researchers use data sources obtained from primary data, namely data obtained directly from the object of research. The sampling technique uses a non-probability sampling approach with a purposive sampling technique. The collected data were analyzed using SPSS software version 26. The results showed that the variables of performance expectations, trust, experiential expectations, and parasocial interactions had a positive and significant effect on the intention to donate variable. Meanwhile, the effort expectancy and facilitating conditions variables have no effect on the intention to donate variable.